POTOMORPHALOGICAL DIFFERENTIAL DIAGNOSTICS OF PULLOROSIS AND STREPTOCOCCOS DISEASES IN POULTRY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The article describes the co-occurrence, clinical signs and pathomorphological changes of pullorosis and streptococcal diseases in chickens. Information on pathological changes in the body of birds and their differential diagnosis is given.